New record of the genus Israelimeria Weiner & Kaprus’, 2005 (Collembola: Neanuridae: Pseudachorutinae) from Iran, with description of a new species - Alijani, Masoumeh; Shayanmehr, Masoumeh; Skarżyński, Dariusz; Piwnik, Agata; Smolis, Adrian (Zootaxa, 2015)
Israelimeria persica sp. nov. is described from Iran. The genus Israelimeria can be easily identified due to a reduction of the number of eyes and the complete absence of the postantennal organ and the furca. The new taxon, and also the second species of the genus, differs from I. poliakovae Weiner & Kaprus’, 2005, known only from Judean Mts. in Israel, in size and shape of mandibles and many chaetotactic characters, especially number of setae in ocular area of the head, ventral tube, subcoxae “1” and microchaetae number in furcal area.